Development and Validation of an HPLC Method for Simultaneous Quantification of Clopidogrel Bisulfate, Its Carboxylic Acid Metabolite, and Atorvastatin in Human Plasma: Application to a Pharmacokinetic Study - Octavian Croitoru; Adela-Maria Spiridon; Ionela Belu; Adina Turcu-Ştiolică; Johny Neamţu (Journal of Analytical Methods in Chemistry)
A simple, sensitive, and specific reversed phase liquid chromatographic method was developed and validated for simultaneous quantification of clopidogrel, its carboxylic acid metabolite, and atorvastatin in human serum. Plasma samples were deproteinized with acetonitrile and ibuprofen was chosen as internal standard. Chromatographic separation was performed on an BDS Hypersil C18 column (250 × 4.6 mm; 5 μm) via gradient elution with mobile phase consisting of 10 mM phosphoric acid (sodium) buffer solution (pH = 2.6 adjusted with 85% orthophosphoric acid) : acetonitrile : methanol with flow rate of 1 mL·min−1. Detection was achieved with PDA detector at 220 nm. The method was validated in terms of linearity, sensitivity, precision, accuracy, limit of quantification, and stability tests. Calibration curves of the analytes were found to be linear in the range of 0.008–2 μg·mL−1 for clopidogrel, 0.01–4 μg·mL−1 for its carboxylic acid metabolite, and 0.005–2.5 μg·mL−1 for atorvastatin. The results of accuracy (as recovery) with ibuprofen as internal standard were in the range of 96–98% for clopidogrel, 94–98% for its carboxylic acid metabolite, and 90–99% for atorvastatin, respectively.